The Role of ICT in Curbing Electoral Fraud in Nigeria - Muhammad, Abba Jalo; Moveh, Fred Fudah; Malgwi, Wasinda Joseph; Yahya, Abdulaziz Suleiman (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
This study centered on preferences of electoral fraud as a major challenge to political development in Nigeria. An electoral fraud is an illegal interference with the process of election that interferes with the mandate of the people. The statement of the problem is the abuse of the democratic principle which has led to elections losing its capacity to determine who will represent the people. This development has resulted to the masses losing confidence in the democratic exercise and the morale to vote has been killed because of the “so or die” nature of elections. This study delves into the nature and character of electoral fraud in Nigeria. The study was guided by its objectives which state that, perception of the electoral fraud has impact on Nigerian elections, electoral fraud and electoral participation in Nigeria and political instability and social disorder in Nigeria resulting from electoral fraud. The focus of this study is to examine the role of ICT in preventing electoral fraud and investigate the ugly perfection of electoral fraud. The Marxist theory of the state was adopted as the theoretical framework and sources of data collected was mainly primary data and analysis using SPPS. This research concluded that the high rate of electoral fraud is adversely undermining the process of free and fair election. Finally, this study recommended that for a total consolidation of the nascent democracy in Nigeria all hands must be on deck to eliminate electoral fraud in Nigeria. Keywords: